Effects of intravenous glucocorticoids on postoperative delirium in adult patients undergoing major surgery: a systematic review and meta-analysis with trial sequential analysis - Chengwei Li; Zheng Zhang; Lin Xu; Xiaojie Lin; Xinyi Sun; Jianjun Li; Penghui Wei (BMC Anesthesiology, 2023)
Abstract Background The effects of intravenous glucocorticoids on postoperative delirium (POD) in adult patients undergoing major surgery remain controversial. Therefore, we conducted this meta-analysis to assess whether intravenous glucocorticoids can decrease POD incidence in the entire adult population undergoing major surgery and its association with patients age, type of surgery, and type of glucocorticoid. Methods We searched the relevant literature published before November 3, 2023, through Cochrane Library, PubMed, Embase, and Web of Science. The primary outcome was POD incidence. The risk ratio for the primary outcome was calculated using the Mantel–Haenszel method. The secondary outcomes included 30-day mortality, length of hospital stay, ICU duration, mechanical ventilation duration, and occurrence of glucocorticoid-related adverse effects (e.g., infection and hyperglycemia). This meta-analysis was registered in PROSPERO: CRD42022345997. Results We included eight randomized controlled studies involving 8972 patients. For the entire adult population undergoing major surgery, intravenous glucocorticoids reduced the POD incidence (risk ratio = 0.704, 95% confidence interval, 0.519–0.955; P = 0.024). However, subgroups defined by type of surgery showed differential effects of glucocorticoids on POD. Intravenous glucocorticoids can not reduce POD incidence in adult patients undergoing cardiac surgery (risk ratio = 0.961, 95% confidence interval, 0.769–1.202; P = 0.728), with firm evidence from trial sequential analysis. However, in major non-cardiac surgery, perioperative intravenous glucocorticoid reduced the incidence of POD (risk ratio = 0.491, 95% confidence interval, 0.338–0.714; P < 0.001), which warrants further studies due to inconclusive evidence by trial sequence analysis. In addition, the use of glucocorticoids may reduce the mechanical ventilation time (weighted mean difference, -1.350; 95% confidence interval, -1.846 to -0.854; P < 0.001) and ICU duration (weighted mean difference = -7.866; 95% confidence interval, -15.620 to -0.112; P = 0.047). Conclusions For the entire adult population undergoing major surgery, glucocorticoids reduced the POD incidence. However, the effects of glucocorticoids on POD appear to vary according to the type of surgery. In patients receiving major non-cardiac surgery, glucocorticoid may be an attractive drug in the prevention of POD, and further studies are needed to draw a definitive conclusion. In cardiac surgery, intravenous glucocorticoids have no such effect.